Informed design of educational technologies in higher education enhanced learning and teaching - Olofsson, Anders D., 1973-; Lindberg, J. Ola, 1966- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book presents recent and important theoretical and practical advances in educational technology design in higher education, examining their possibilities for enhancing teaching and learning"--Provided by publisher.